Modeling of PV panels performance based on datasheet values for solar micro energy harvesting - Rasool, F. (Institute of Electrical and Electronics Engineers Inc., 2017)
Typically photovoltaic (PV) panel datasheets provide the electrical parameters at only Standard Test Condition (STC) i.e. at irradiance of 1000 W/m2 and cell temperature of 25°C. However, the PV panels operate at various operating conditions. Therefore the datasheet information is not sufficient to determine its behavior. There is a need of a novel model to predict the behavior of PV panel under all conditions. Single Mechanism Five Parameters (1M5P) model uses datasheet values along with series and parallel resistance of the PV panel. The basic equations of the model and parameters extraction from datasheet are shown. The advantage of this model is that it only requires the minimum parameters from datasheet. Furthermore, it can predict the behavior of PV panel under all operating conditions and can be used for solar micro energy harvesting. At STC, the model is validated with both datasheet and experimental values with difference less than 5. © 2016 IEEE.